Influence of liquid hydrogen and nitrogen on MHD triple diffusive mixed convection nanoliquid flow in presence of surface roughness - Patil, P.M.; Shashikant, A.; Hiremath, P.S. (International journal of hydrogen energy, 2018)
An innovative study of influence of surface roughness and nanoparticles on mixed convection flow is considered in presence of liquid hydrogen and liquid nitrogen. In fact, in order to understand the effects of surface roughness and nanoparticles on the flow characteristics of MHD triple diffusive mixed convection nanoliquid flow along an exponentially stretching rough surface, the flow problem is modelled in terms of highly nonlinear partial differential equations subject to the appropriate boundary conditions. Then, those equations are made non-dimensional with the application of non-similar transformations. The resultant nonlinear dimensionless coupled partial differential equations with boundary constraints are solved by using the Quasilinearization technique in combination with the implicit finite difference scheme. The liquid hydrogen and liquid nitrogen are considered as species concentration components. The surface roughness is modelled by a sine wave representation and hence the sinusoidal variations have been observed in gradients such as skin-friction coefficient, heat and mass transfer rates. It is observed that the effects of surface roughness on the skin-friction coefficient are more prominent near the origin than that in downstream. The addition of nanoparticles into the ambient ordinary fluid enhances the skin-friction coefficient and reduces the magnitude of wall heat transfer rate for both cases of smooth and rough surfaces. The rapid variations have been observed in the wall mass transfer rate due to the surface roughness in comparison to that of skin-friction coefficient and wall heat transfer rate. Further, the magnitude of wall mass transfer rate of liquid nitrogen is higher than that of liquid hydrogen. •Effects of surface roughness & nanoparticles on flow characteristics are analyzed.•Magnitude of mass transfer rate of liquid nitrogen is higher than liquid hydrogen.•Nanoparticles enhance the skin-friction for smooth as well as rough surfaces.•On introduction of nanoparticles the magnitude of heat transfer rate reduces.•Effects of surface roughness are more prominent on the mass transfer rate.